배추 Glutathione S-transferase 전사체의 Real-time PCR을 이용한 정량법 - 이동우(Dong-Woo Lee); 김을환(Eul-Hwan Kim); 강민희(Min-Hee Kang); 박영두(Young-Doo Park); 윤병수(Byoung-Su Yoon) (Weon'ye gwahag gi'sulji, 2008)
십자화과 채소에서 glutathione S-transferase(GST)는 glutathione과 sulforaphane(1-isothiocyanato-4-methylsulfinyl butane)을 포함하는 isothiocyanate(ITC)의 반응을 촉매 하 여 ITC-glutathione을 생성하게 한다. 이 대사회로에서 GST 의 음성조절은 식물체내에 ITC의 축적을 일으킬 것으로 기 대되었다. 본 연구는 Brassica 속에 속하는 채소류에서 실시 간 역전사 PCR법을 사용하여 GST의 발현수준을 정량할 수 있는 분석법을 개발하였다. GST 특이 정량 PCR은 GST유 전자를 가진 클론 DNA를 사용하여 확립하였으며, 이 정량 역전사 PCR법의 이용을 시험하기 위하여, 배추의 GST 형 질전환체에 대하여 그리고 다양한 십자화과 채소들에 대하 여 독립적인 평가를 실시하였다. 이 평가에서 GST 특이 cDNA의 양은 108 분자에서 102 분자의 수준까지 성공적으 로 측정되었으며, 또한 Brassica속에 속하는 다양한 생물 종 에서 GST발현을 정량적으로 분석할 수 있었다. 이 GST 정 량 역전사 PCR법은 다양한 채소류의 비교분석이나, ITC 대 사의 생리학적 연구들 또는 배추의 GST 형질전환체의 선발 등에 응용될 수 있을 것이다. In cruciferous vegetables, glutathione s-transferase (GST) catalyze the reaction with glutathione and isothiocyanate (ITC) including sulforaphane (1-isothiocyanato-4-methylsulfinyl butane), to form ITC-glutathione. In this pathway the down-regulation of GST is expected to accumulate ITC in plant body. In this study, we developed a quantitative analysis method of GST expression level using real-time RT-PCR in vegetables belonged to the genus Brassica. GST-specific quantitative PCR was established with cloned DNA encoding GST gene. To test utility of quantitative RT-PCR system we have conducted two independent evaluations for GST-transgenic chinese cabbage and for various cruciferous vegetables. With these studies, the quantities of GST-specific cDNA were successfully estimated from 108 to 102 molecules, and GST-expressions from various species of genus Brassica could be also quantitatively analyzed. GST quantitative RT-PCR could be applied in comparative analysis among Brassicas or physiological studies of isothiocyanate metabolism or a selection method for GST-transgenic chinese cabbage, etc. KCI Citation Count: 0